Cyber Law in the Digital Era: Challenges and Legal Developments in Developing Countries - Arief Fahmi Lubis (Edujavare Publishing, 2025)
The rapid expansion of digital technology has significantly influenced the evolution of cyber law, particularly in developing countries that face complex challenges in adapting their legal systems to the digital era. This study aims to analyze the development and key challenges of cyber law in the context of digital transformation, with a focus on developing nations. The research employs a normative legal method using statutory, conceptual, and comparative approaches, relying on secondary data derived from legal documents, international reports, and academic literature. The findings reveal that although many developing countries have established legal frameworks addressing cybercrime, electronic transactions, and data protection, these regulations often remain fragmented and insufficiently enforced. Major challenges include jurisdictional issues, limited institutional capacity, lack of technical expertise, and the tension between cybersecurity and the protection of human rights. Furthermore, the study highlights the growing influence of global standards, particularly in data protection, while emphasizing the need for contextual adaptation in local legal systems. The study concludes that strengthening cyber law requires a comprehensive and adaptive approach that integrates legal reform, institutional development, and international cooperation to ensure both digital security and the protection of fundamental rights.